A DESIGN of THE IoT-BASED HOME ELECTRONIC DEVICE CONTROLLER WITH FUZZY METHOD USING RASPBERRY PI - Daren Kurniawan Widodo; Dram Renaldi (ALGOR, 2020)
Technology develops rapidly in the present era, among them is the controller system or controllers system. One of the uses of IoT technology is as a media control system and monitoring of a wide range of electronic devices with the concept to expand the connectivity of Internet networks connected to the global network. In this discussion aims to design and build a controlling system by utilizing simple Internet Of Things technology, using a Raspberry Pi. The Software used in Raspberry Pi consisted of top Raspbian as an operating system. Utilizing simple IoT technologies that control this electronic device through mobile web embedded in the Mini PC controller of Raspberry Pi devices. To give a command that will be in process on Raspberry is by programming using Python programming language. The User interface on fan control is the buttons such as those found in the fan coupled with information on fan status and room temperature. Based on the results of research and discussion can be concluded the system can control remotely through the Internet network to turn off/turn on lights and home electronic devices.